2011
DOI: 10.1016/j.rehab.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life in stroke patients with hemiplegia

Abstract: Quality of life at 2 years is significantly impaired in stroke survivors and seems more difficult to predict than functional independence. However, in addition to these objective results, our interviews suggest that receiving adequate social support might be as important to patients as recovering independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 29 publications
9
43
0
1
Order By: Relevance
“…Regarding the results of this study, the quality of life in the physical and mental health dimensions had a significant difference in the case and control groups, which is consistent with Agh study (Agh, 2014). Also in Laurent research results showed life satisfaction and quality of life were significantly impaired in stroke patients, compared with controls and Quality of life was strongly correlated with functional independence and depressive mood (Laurent, 2011). A study by Barkhordari, et al which aimed to investigate the relationship between quality of life and the accidents, the results showed that the mean scores of quality of life there is a significant difference between the two groups in two physical pain and role limitations (Barkhordari, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the results of this study, the quality of life in the physical and mental health dimensions had a significant difference in the case and control groups, which is consistent with Agh study (Agh, 2014). Also in Laurent research results showed life satisfaction and quality of life were significantly impaired in stroke patients, compared with controls and Quality of life was strongly correlated with functional independence and depressive mood (Laurent, 2011). A study by Barkhordari, et al which aimed to investigate the relationship between quality of life and the accidents, the results showed that the mean scores of quality of life there is a significant difference between the two groups in two physical pain and role limitations (Barkhordari, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…The quality of life of our patients remained altered 1 year after the stroke, as in previous studies, 11,18,23 particularly for vitality and physical and emotional states. Scores on the SF-36 were correlated with scores on the FIM scale despite their broad distribution.…”
Section: Discussionsupporting
confidence: 82%
“…Earlier studies have also indicated that the most significant predictors of HRQOL are functional status and depression (3,4,10,(16)(17)(18)(19)25,36), although a study demonstrated a more generalized adverse effect on HRQOL than functional disabilities (37), and some who have demonstrated disability alone explained little regarding the variance in the QOL (2,38). The results produced from the current study demonstrated that the anxiety and depression scores in patients were significantly higher compared with those in controls.…”
Section: Discussionmentioning
confidence: 99%